2018
DOI: 10.1186/s13568-018-0676-2
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomer discrimination in β-phenylalanine degradation by a newly isolated Paraburkholderia strain BS115 and type strain PsJN

Abstract: Despite their key role in numerous natural compounds, β-amino acids have rarely been studied as substrates for microbial degradation. Fermentation of the newly isolated Paraburkholderia strain BS115 and the type strain P. phytofirmans PsJN with β-phenylalanine (β-PA) as sole nitrogen source revealed (S)-selective transamination of β-PA to the corresponding β-keto acid by both strains, accompanied by substantial formation of acetophenone (AP) from spontaneous decarboxylation of the emerging β-keto acid. While t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…It was demonstrated that AcPhe depletion via evaporation in bioreactor was not notable (data not shown). AcPhe decreasing during fermentation was also reported by Buß et al ( 2018a ), who discussed the possibility of bacterial metabolization of AcPhe. Besides, it was shown that alcohol dehydrogenases (ADH) from Lactobacillus kefir accepts AcPhe and converts it to ( R )-alcohol (Yun et al 2003 ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It was demonstrated that AcPhe depletion via evaporation in bioreactor was not notable (data not shown). AcPhe decreasing during fermentation was also reported by Buß et al ( 2018a ), who discussed the possibility of bacterial metabolization of AcPhe. Besides, it was shown that alcohol dehydrogenases (ADH) from Lactobacillus kefir accepts AcPhe and converts it to ( R )-alcohol (Yun et al 2003 ).…”
Section: Discussionsupporting
confidence: 75%
“…from extremophile microorganisms. Buß et al ( 2018a ) studied β-phenylalanine degradation during fermentation of Paraburkholderia . Cultivation of Arthrobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…ω-TA activity against 14 has been reported by Mathew et al for ω-TABG, with 50% relative activity in comparison with 13 [30]. A recent study by Buß et al explained the lack of ω-TA activity against 14 (by an ω-TA that was highly active against 13) by sterice hindrance caused by the additional carbon atom located between the amino group and phenyl group [36]. Several substituted derivatives of β-phenylalanine are converted as well.…”
Section: Substrate Specificity and Enantioselectivitymentioning
confidence: 83%
“…Notably, it is difficult to conclude that BaH showed (R)-selectivity since in this study, crude extract was applied. There is a possibility that (R) converted to (S)-enantiomer via enzymatic racemization [36], and then the latter was subjected to ω-TA activity. On the other hand, (R)-preference towards 13r in compare to 13s leads to another hypothesis, in which both R and S transaminases are present in crude extract.…”
Section: Substrate Specificity and Enantioselectivitymentioning
confidence: 99%
See 1 more Smart Citation